LEGALITAS ORGANISASI BARU DI LUAR WADAH TUNGGAL ORGANISASI PROFESI DOKTER DI INDONESIA DALAM TINJAUAN YURIDIS - Made Agus Mahendra Inggas; Dian Ratu Ayu Uswatun Khasanah; Ronald Jolly Pongantung (Jurnal Ilmiah Dinamika Hukum, 2023)
The Association of Indonesian Doctors has been formed and declared in a Decree of the Ministry of Law and Human Rights, Number AHU-003638.AH.01.07.2022. The Indonesian Doctors Association is no longer the sole forum for medical organizations in Indonesia. The study of the legality of this new association and the study of the organization of the Indonesian Doctors' Association have violated the right to associate and human rights because it is the sole forum for the medical professional organization which is the focus of the problem raised by the author. The study uses a normative juridical approach to seek answers with certainty and legal certainty through existing legal theories, norms and legislation. The conclusions obtained are that in order to protect patients, improve service quality, and ensure legal and statutory certainty, the medical professional association or organization must be one. Determination of quality and service, competency standards, and professional ethics must come from a professional organization. With a noble purpose, a single professional organization does not violate the law on association and human rights. The presence of a new medical society organization will not interfere with the position of the Indonesian Doctors Association as a professional organization. The suggestion from this study is that new organizations such as the Association of Indonesian Doctors must synergize and become the task force for the Indonesian Doctors Association in controlling the running of the organization while simultaneously providing a driving force for services to the Indonesian people. Key words: Professional organizations; Constitution; Medical practice